2001
DOI: 10.1037/0021-9010.86.5.954
|View full text |Cite
|
Sign up to set email alerts
|

Explaining employees' health care costs: A prospective examination of stressful job demands, personal control, and physiological reactivity.

Abstract: The authors tested the ability of stressful demands and personal control in the workplace to predict employees' subsequent health care costs in a sample of 105 full-time nurses. Both subjective and objective measures of workload demands interacted with personal control perceptions in predicting the cumulative health care costs over the ensuing 5-year period. Tonic elevations in salivary cortisol, moreover, mediated the effects of demands and control on health care costs. Neither the job demands variables nor p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
109
0
4

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(118 citation statements)
references
References 37 publications
4
109
0
4
Order By: Relevance
“…Research using physiological recovery indicators and more objective health indicators point into a similar direction. In a sample of nurses, Ganster et al (36) found that elevated cortisol levels after (but not during) work predicted health care costs 5 years later. In a more recent study, Stewart et al (37) showed that poorer blood pressure recovery among healthy adults after they conducted psychologically challenging tasks predicted elevated blood pressure levels 3 years later (also when initial blood pressure levels and possible confounders such as body mass index, education, and lifestyle factors were controlled).…”
Section: Sustained Activation Incomplete Recovery and Chronic Load Rmentioning
confidence: 99%
“…Research using physiological recovery indicators and more objective health indicators point into a similar direction. In a sample of nurses, Ganster et al (36) found that elevated cortisol levels after (but not during) work predicted health care costs 5 years later. In a more recent study, Stewart et al (37) showed that poorer blood pressure recovery among healthy adults after they conducted psychologically challenging tasks predicted elevated blood pressure levels 3 years later (also when initial blood pressure levels and possible confounders such as body mass index, education, and lifestyle factors were controlled).…”
Section: Sustained Activation Incomplete Recovery and Chronic Load Rmentioning
confidence: 99%
“…Karasek (1979) initially proposed that the negative effects of job demands would interact with job control whereby the most strain is experienced in a low-control high-demand situation. In a sense, higher job control can negate some of the effects of certain job stressors whereby high control tends to result in a weaker or null relationship between demands and negative outcomes (Dwyer & Ganster, 1991;Ganster, Fox, & Dwyer, 2001). Therefore, midwives' experience of higher job control may moderate the relationship between other workplace stressors (i.e., workload, work scheduling, role conflict) and the outcome measures (i.e., strain, burnout, and work-life balance).…”
Section: Stress and Burnout 10mentioning
confidence: 99%
“…Workload and social support were found to have a direct relationship with emotional exhaustion (Tummers et al, 2001) and another study found that decision latitude was negatively associated with absenteeism measured at the nursing unit level (Seago, 1996). The model has also predicted health care costs incurred by the sample of nurses, although it did not predict mental health as measured by distress and well-being (Ganster et al, 2001). Additionally, an expanded model that included active coping predicted burnout among nurses (de Rijk et al, 1998).…”
Section: Applicability To Nursingmentioning
confidence: 99%
“…Ganster, Fox and Dwyer (2001) recognized that nursing is a good occupation in which to study the JDC model because of the naturally occurring variations in demands and control within the profession. Indeed, samples of nurses have been used in tests of both the JDC and JDC-S models (Bourbonnais et al 1999;de Rijk et al, 1998;Fox et al, 1993;Ganster et al, 2001;Morgan, Semchuk, Stewart & D"Arcy, 2002;Laschinger, Finegan & Shamian, 2001;Tummers et al, 2001).…”
Section: Applicability To Nursingmentioning
confidence: 99%
See 1 more Smart Citation